Marriage Properties Sharing Based on Islamic Law - Sudirman A. Dg. Mataro; M. Taufan B; Ermawati Ermawati (State Institute for Islamic Studies Palu, 2021)
The aim of this study is to discuss the Sharing of Assets as a Result of Divorce in the Palu Religious Court. This study used qualitative research methods with an emphasis on juridical analysis studies/ The data was gathered through observation, interviews, and documentation. The data analysis technique that the researcher uses is data reduction, data presentation, data verification and conclusion. This study found that, the distribution of shared assets in the Palu Religious Court, the Panel of Judges in completing the distribution of assets referred to Article 35 paragraph (1) of Law Number 1 of 1974 and KHI in article 97. In determining and granting the plaintiff's claim and the plaintiff's reconstruction which contains the Determination of joint assets according to the provisions of the marriage law, that the assets obtained during marriage become joint property. In a legal juridical sense, the understanding of shared property is the property of husband and wife obtained during marriage.